Pengaruh Model Learning Cycle 5E Berbantuan E-LKPD Berbasis Multirepresentasi dalam Pembelajaran IPA terhadap Higher Order Thinking Skills Siswa SMP - Isna Rahmi Firdiana; Supeno; Rusdianto (PendIPA Journal of Science Education, 2023)
This study aimed to collect data for two reasons: (1) How the learning cycle 5E model assisted by multi representation-based E-LKPD in science learning has an effect on HOTS of junior high school students, and (2) How far the use of the learning cycle 5E model assisted by multi representation-based E-LKPD in the subject of science increases the HOTS of junior high school students. The implementation of the research was taking place in the even semester of TP 2022/2023 at SMPN 2 Panti, Jember. Classes VIII B and C were assigned as the experimental and control samples in this study, respectively. Data were collected by pre-and post-testing. While 3 types of tests in analyzing data include normality test, independent sample t-test, and n-gain through SPSS statistics. In the effect test using the independent sample t-test, a confidence level (two-tailed) of 0.000 < 0.05 was generated, so it can be said that students’ HOTS were significantly different prior to and following treatment. The result of increasing higher-order thinking skills using the n-gain test is a medium category increase in students’ HOTS, which is 0.4635. In this case, it can be decided that the learning cycle 5E model assisted by multi representation-based E-LKPD in science learning has an effect on HOTS and helps junior high school students’ HOTS develop into a medium category.